The Impact of Cultural Elements in Cross-Cultural Business Negotiations. A Multiple-Case Study of Finnish and Mexican business negotiations - Virkanen, Katja (My University, 2008)
The purpose of the study was to analyse the influence of culture in Finnish-Mexican business negotiations. Therefore, the main objective for the study was to understand and compare cultural differences, as well as the influence of time and communication in cross-cultural business negotiations. The presumption for the study was that there are more differences than similarities among Finnish and Mexican cultures, which were also supported in the study findings. The framework of the study consisted of two main parts. Firstly, the cultural aspects influencing the cross-cultural business negotiations were discussed. Here the focus was to examine Hofstede’s (1980, 2001) cultural dimension, issues related to the way people in different cultures view time, and the importance of communication in cross-cultural negotiations. Secondly, the business negotiation process model constructed for this study was analysed. This model was based on two separate process models by Simintiras and Thomas (1998), and Ghauri (1996) in order to accomplish a more suitable model for this study. In the empirical part the methodology used was qualitative case studies. Totally eight in-depth interviews were conducted, four of them represented Finnish and the other four Mexican business people. All of the respondents had at least ten years of experience in cross-cultural business negotiations. The theoretical part was continuously reflected to the findings in order to make comparisons between them, but also in order to accomplish some new knowledge. The findings of the study pointed out the importance of culture in cross-cultural business negotiations, as there were found differences between Finns and Mexicans in each stage of the negotiation process model. Thus, the cultural differences should be considered carefully before entering cross-cultural business negotiations.
Keywords: cross-cultural business negotiations; negotiation process; culture; cultural Dimensions; time; communication; Finland; Mexico; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|